Alterations of the colonic flora and their effect on the hydrogen breath test. Issue 7 (July 1978) - Gilat, T; Ben Hur, H; Gelman-Malachi, E; Terdiman, R; Peled, Y
Abstract : The hydrogen breath test was performed by ingestion of 20 g lactulose and analysis of end-expiratory air. Eighteen patients undergoing colonoscopy, 17 receiving antibiotics, 12 prepared for colon surgery, and 15 controls were examined. The test was repeated under control conditions in the treated patients. Eleven of 55 subjects failed to produce significant amounts of hydrogen under control conditions. This 20% proportion of non-hydrogen producers is much higher than that reported by other investigators. The hydrogen production was very markedly depressed after preparation for colonscopy and antibiotic therapy. The effect of neomycin and enemata as used in preparation for colon surgery was less marked. Hydrogen production by the colonic flora is thus subject to individual variations and may be affected by various therapeutic regimens. All these may cause false negative results when using the hydrogen breath test to evaluate carbohydrate absorption. The test should therefore not be performed for a considerable time after therapeutic manipulation of the colonic flora.